Use of additivies in diets for piglets in nursing stage: a review (Research, Society and Development, 2020)
The use of additives in diets for weaned piglets in industrial pig farming aims to reduce the use of antibiotics in this production, besides improving intestinal health and animal’s performance. Therefore, this study aimed to elaborate a bibliographic review on the main additives used in diets for piglets in the nursery phase. The additives acts as pro and prebiotics, which are essential in the nursery phase due to the health challenges that the animals are exposed, since they promote some health benefits for the animals. The success in the use of additives in the nursery phase is related to the dosage to be used and mainly to the challenges levels to which the animals are exposed. Some Research results in this area indicate that additives are more efficient in more challenged animals, which justifies the variability of results found in the literature. Other studies demonstrate that the additives action mechanism can reduce the use of antibiotic in the piglet’s diets in the nursery phase, in addition to adding better performance results regarding weight gain, feed consumption and feed conversion. According to the review carried out, it is concluded that the use of additives in piglets diets during the nursing period, can improve productive indexes of the animals, in addition to being taught as alternatives to the use of antibiotics.